β-carbolines that enhance GABAA receptor response expressed in oligodendrocytes promote remyelination in an in vivo rat model of focal demyelination - Cisneros-Mejorado, Abraham Jotssel; Ordaz, Rainald Pablo; Garay, Edith; Arellano, Rogelio O. (Frontiers in Cellular Neuroscience, 2024)
Demyelination is typically followed by a remyelination process through mature oligodendrocytes (OLs) differentiated from precursor cells (OPCs) recruited into the lesioned areas, however, this event usually results in uncompleted myelination. Potentiation of the remyelination process is an important target for designing effective therapeutic strategies against white matter loss. Here, it was evaluated the remyelinating effect of different β-carbolines that present differential allosteric modulation on the GABAA receptor expressed in OLs. For this, we used a focalized demyelination model in the inferior cerebellar peduncle (i.c.p.) of rats (DRICP model), in which, demyelination by ethidium bromide (0.05 %) stereotaxic injection was confirmed histologically by staining with Black-Gold II (BGII) and toluidine blue. In addition, a longitudinal analysis with diffusion-weighted magnetic resonance imaging (dMRI) was made by computing fractional anisotropy (FA), apparent diffusion coefficient (ADC) and diffusivity parameters to infer i.c.p. microstructural changes. First, dMRI analysis revealed FA decreases together with ADC and radial diffusivity (RD) increases after demyelination, which correlates with histological BGII observations. Then, we evaluated the effect produced by three allosteric GABAA receptor modulators, the N-butyl-β-carboline-3-carboxylate (β-CCB), ethyl 9H-pyrido[3,4-b]indole-3-carboxylate (β-CCE), and 4-ethyl-6,7-dimethoxy-9Hpyrido [3,4-b]indole-3-carboxylic acid methyl ester (DMCM). The results indicated that daily systemic β-CCB (1 mg/Kg) or β-CCE (1 mg/Kg) administration for two weeks, but not DMCM (0.35 mg/Kg), in lesioned animals increased FA and decreased ADC or RD, suggesting myelination improvement. This was supported by BGII staining analysis that showed a recovery of myelin content. Also, it was quantified by immunohistochemistry both NG2 + and CC1 + cellular population in the different experimental sceneries. Data indicated that either β-CCB or β-CCE, but not DMCM, produced an increase in the population of CC1 + cells in the lesioned area. Finally, it was also calculated the g-ratio of myelinated axons and observed a similar value in those lesioned animals treated with β-CCB or β-CCE compared to controls. Thus, using the DRICP model, it was observed that either β-CCB or β-CCE, positive modulators of the GABAA receptor in OLs, had a potent promyelinating effect.